Evaluation of the VIDAS Anti-HCV Assay for Detection of Hepatitis C Virus Infection - Hyun, Jungwon; Ko, Dae-Hyun; Kang, Hee Jung; Whang, Dong Hee; Cha, Young Joo; Kim, Hyun Soo (Annals of laboratory medicine, 2016)
Anti-hepatitis C virus antibody (anti-HCV) assays are recommended for screening HCV-infected persons. The VIDAS Anti-HCV Assay (bioMérieux, France), based on the enzyme-linked fluorescence test principle, was recently introduced in Korea. We evaluated the clinical performance of the VIDAS assay. One hundred HCV-positive and 1,002 HCV-negative blood samples confirmed by Architect anti-HCV (Abbott Laboratories, USA) and COBAS TaqMan HCV real-time PCR (Roche Diagnostics, USA) or the Procleix Ultrio Plus Assay (Gen-Probe Incorporated, USA) were obtained from the Human Serum Bank (HSB) and tested by VIDAS. In case of discrepant results, we conducted a recombinant immunoblot assay (RIBA). The agreement rates for known HCV-positive and HCV-negative samples between the VIDAS assay and the HSB testing were 100% (95% confidence interval [CI]: 96.4-100%) and 99.5% (95% CI: 98.8-99.8%), respectively. One of the five discrepant samples was positive for Core 2+ and NS3-2 2+ reactivity, two samples were negative, and the other two were indeterminate regarding NS4 2+ reactivity in RIBA. We observed a significant but weak positive correlation between the titers of VIDAS and Architect assays (r=0.315, P<0.001). The VIDAS anti-HCV assay, developed on the VIDAS automated immunoassay platform based on the ready-to-use, single-sample test concept may be useful in small-to-medium-sized laboratories. It showed good agreement with Architect anti-HCV and COBAS PCR assays and is therefore useful for detection of HCV infection. Weakly test-positive (ambiguous) samples require additional testing by another anti-HCV, RIBA, or HCV RNA assay.